THE THIRD RENAISSANCE IS A PERIOD OF FORMATION OF ENTREPRENEURS AS A SPIRITUALLY MATURE PERSON (Academicia Globe: Inderscience Research, 2022)
This article discusses the forms and features of the manifestation of threats in the process of globalization and their negative impact on the social life of our society.